2016
DOI: 10.3390/ijerph13111147
|View full text |Cite
|
Sign up to set email alerts
|

The Safety Attitudes of Senior Managers in the Chinese Coal Industry

Abstract: Introduction: Senior managers' attitudes towards safety are very important regarding the safety practices in an organization. The study is to describe the current situation of senior managers' attitudes towards safety in the Chinese coal industry. Method: We evaluated the changing trends as well as the reasons for these changes in the Chinese coal industry in 2009 and in 2014 with 168 senior manager samples from large Chinese state-owned coal enterprises. Evaluations of 15 safety concepts were performed by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…16 In China's occupational-health and safety realm, evidence of such increasing stringency is mixed. The two primary laws on workplace safety and prevention of occupational diseases have each been strengthened twice in the last decade, but enforcement is still believed to lag (Zhou 2018), with possible exceptions such as in the coal mining industry (Zhang et al 2016). On environment, laws, regulations, and enforcement have developed considerably in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…16 In China's occupational-health and safety realm, evidence of such increasing stringency is mixed. The two primary laws on workplace safety and prevention of occupational diseases have each been strengthened twice in the last decade, but enforcement is still believed to lag (Zhou 2018), with possible exceptions such as in the coal mining industry (Zhang et al 2016). On environment, laws, regulations, and enforcement have developed considerably in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Managers' attitudes to safety and miners' roles affect health outcomes [52,114]. Psychological stress levels in Australian miners were higher than in non-mine workers, with alcohol use, work role (as managers), level of work satisfaction, financial factors and job insecurity contributing factors.…”
Section: Social and Managerial Risksmentioning
confidence: 99%
“…Hui et al measured food handlers' attitudes towards food safety through a scale of 14 items [13]. Zhang et al studied the safety attitude of senior managers in the coal mining industry and concluded that it played a very important role in the safe operation of a mining organization [14].…”
Section: Introductionmentioning
confidence: 99%